Single-walled carbon nanohorn (SWNH) aggregates inhibited proliferation of human liver cell lines and promoted apoptosis, especially for hepatoma cell lines - Zhang JQ (Dove Medical Press, 2014)
Jinqian Zhang,1,* Qiang Sun,2,* Jian Bo,3 Rui Huang,4 Mengran Zhang,1 Zhenglin Xia,4 Lili Ju,5 Guoan Xiang4 1Institute of Infectious Diseases, Beijing Ditan Hospital, Capital Medical University, Beijing, People's Republic of China; 2Department of Nephrology, Beijing Children's Hospital, Capital Medical University, Beijing, People's Republic of China; 3Department of Hematology, Chinese PLA (People's Liberation Army) General Hospital, Beijing, People's Republic of China; 4Department of General Surgery, The Second People's Hospital of Guangdong Province, Southern Medical University, Guangzhou, People's Republic of China; 5Department of Neurobiology, Beijing Institute for Brain Disorders, Beijing Center of Neural Regeneration and Repair, Key Laboratory for Neurodegenerative Diseases of the Ministry of Education, Capital Medical University, Beijing, People's Republic of China *These authors contributed equally to this work Abstract: Single-walled carbon nanohorns (SWNHs) may be useful as carriers for anticancer drugs due to their particular structure. However, the interactions between the material itself and cancerous or normal cells have seldom been studied. To address this problem, the effects of raw SWNH material on the biological functions of human liver cell lines were studied. Our results showed that unmodified SWNHs inhibited mitotic entry, growth, and proliferation of human liver cell lines and promoted their apoptosis, especially in hepatoma cell lines. Individual spherical SWNH particles were found inside the nuclei of human hepatoma HepG2 cells and the lysosomes of normal human liver L02 cells, implying that SWNH particles could penetrate into human liver cells and the different interacted mechanisms on human normal cell lines compared to hepatoma cell lines. Further research on the mechanisms and application in treatment of hepatocellular carcinoma with SWNHs is needed. Keywords: single-walled carbon nanohorns, SWNHs, cell proliferation, cell apoptosis, hepatocellular carcinoma, nucleus, lysosome